User Acceptance of the E-Perolehan System Among Government Users in Malaysia - George Patrick @ Marimuthu (2007)
The study of user acceptance of new technology and technology innovation is considered to be one of the mature studies in the field of Information Systems (IS). User acceptance refers to the willingness of the user group to employ information technology for tasks the technology is designed to support. This study looked into user acceptance of the eperolehan system at the individual level in the context of business-to-consumer (B2C). eperolehan is an electronic procurement system that converts manual procurement processes in the Government machinery to electronic procurement processes on the Internet. The study involved the use of an intention-based model and the Technology Acceptance Model (TAM) as its nomological framework. The constructs or variables of this study were subsumed in the quality dimension of the DeLone and McLean Model of IS Success. This study framed ten (10) independent variables and two (2) dependent variables. The ten independent variables were perceived usefulness (subsumed in the system quality dimension), trust, perceived ease of use and perceived risk (information quality dimension), assurance, responsiveness and facilitating conditions (service quality dimension) and web design quality (system, information and service). The two dependent variables were Intention to Transact and Actual Transaction Behavior. The instruments utilized in this study were adapted and adopted from established instruments in the context of the eperolehan system. This study employed a survey using self-administered questionnaires which were distributed to 358 respondents (government users) of the eperolehan system from a sampling frame of 1150 government users from 230 Pusat Tanggungjawab (procuring unit) of the 28 government ministeries and departments located in Klang Valley and Putrajaya. The data analysis procedures administered in this study generally comprised of descriptive and inferential statistics using the Statistical Package for Social Sciences (SPSS) and a Structural Equation Model (SEM) using LISREL to examine the hypotheses. A competing model was developed which had several path relationships added to the original model and presented a good model fit which enabled the hypotheses to be tested. It was found that perceived usefulness, assurance, facilitating conditions, perceived risk and web design quality (service quality) had significant relationships with lntention to Transact. Meanwhile, perceived ease of use, trust, responsiveness, web design quality (information and system) had insignificant relationships with lntention to Transact. lntention to Transact had a significant relationship with Actual Transaction Behavior. This study addressed several limitations and recommendations for future studies were proposed to encourage further research on user acceptance studies.